2009
DOI: 10.1002/cbf.1597
|View full text |Cite
|
Sign up to set email alerts
|

A JNK inhibitor SP600125 induces defective cytokinesis and enlargement in P19 embryonal carcinoma cells

Abstract: While analyzing the role of c-Jun NH(2)-terminal kinase (JNK) in neurogenesis in P19 embryonal carcinoma cells, we noticed that treatment with SP600125, a JNK inhibitor, increased the cell size markedly. SP600125-induced enlargement of P19 cells was time- and dose-dependent. The increased cell size in response to SP600125 was also detected in B6mt-1 embryonic stem cells. SP600125 treatment inhibited cell growth and increased DNA contents, indicating the inhibition of cell proliferation resulting from endoredup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Up to date, there are contrasting reports about p53 involvement in the SP mechanism of action [ 11 , 13 - 15 , 27 ]. To elucidate this point, three cell lines representing different TP53 status were chosen for further examination: the TP53 wild-type TPC1, the TP53 p.P152L mutant HTC/C3, and the p53 pseudo-null SW1736.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to date, there are contrasting reports about p53 involvement in the SP mechanism of action [ 11 , 13 - 15 , 27 ]. To elucidate this point, three cell lines representing different TP53 status were chosen for further examination: the TP53 wild-type TPC1, the TP53 p.P152L mutant HTC/C3, and the p53 pseudo-null SW1736.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of nuclear abnormalities such as heterochromatic foci, multinucleation and nuclear blebbing, lysosomal compartment expansion and positive γ-H2A.X staining in a large fraction of SP treated HTC/C3 cells ( Supplementary Figure 2 ) confirmed the presence of cellular senescence [ 31 - 32 ]. To date, increases in cell dimensions and in p21 expression following SP treatment have been occasionally reported [ 27 , 33 ]. On the other hand, SP-induced p53-dependent premature senescence has never been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin dependent kinases (CDKs) are the key cell cycle regulators 11 21 . The CDK inhibitor, p21, has been reported to have different expression levels in normal diploid and non-diploid cells (such as cancer cells) as the downstream of the p53 signal pathway 12 21 . Our study reveals that both p21 and p53 expressions are up-regulated in the SP600125-induced tetraploid cells, especially compared with the diploid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results indicate that the small compound SP600125 could induce polyploidization of mammalian cancer cells 11 12 . As a c-Jun N-terminal kinase (Jnk) inhibitor, it is reported that SP600125 can lead to G2/M phase arrest such that G2-to-M phase transition is prevented, and DNA endoreplication occurs directly from the G2 phase 11 13 14 .…”
mentioning
confidence: 96%
“…Another study showed that SP induces defective cytokinesis and enlargement of P19 cells [36]. These results could be used to argue that the SP-induced increase in MOR expression is caused by the presence of increased DNA content and increased stability of the MOR mRNA.…”
Section: Resultsmentioning
confidence: 99%